Material Characterisation and Stratification of Conjunctival Epithelial Cells on Electrospun Poly(ε-Caprolactone) Fibres Loaded with Decellularised Tissue Matrices - Lucy A. Bosworth; Kyle G. Doherty; James D. Hsuan; Samuel P. Cray; Raechelle A. D’Sa; Catalina Pineda Molina; Stephen F. Badylak; Rachel L. Williams (Pharmaceutics, 2021)
The conjunctiva, an under-researched yet incredibly important tissue, plays key roles in providing protection to the eye and maintaining homeostasis of its ocular surface. Multiple diseases can impair conjunctival function leading to severe consequences that require surgical intervention. Small conjunctival defects can be repaired relatively easily, but larger defects rely on tissue grafts which generally do not provide adequate healing. A tissue engineering approach involving a biomaterial substrate capable of supporting a stratified epithelium with embedded, mucin-secreting goblet cells offers a potential solution. As a first step, this study aimed to induce stratification of human conjunctival epithelial cells cultured on electrospun scaffolds composed from poly(ε-caprolactone) (PCL) and decellularised tissue matrix (small intestinal submucosa (SIS) or urinary bladder matrix (UBM)) and held at the air/liquid interface. Stratification, up to 5 cell layers, occurred more frequently on scaffolds containing PCL + UBM. Incorporation of these decellularised tissue matrices also impacted material properties, with significant changes occurring to their fibre diameter, tensile properties, and chemical composition throughout the scaffold structure compared to PCL alone. These matrix containing scaffolds warrant further long-term investigation as a potential advanced therapy medicinal product for conjunctiva repair and regeneration.